JUSTICE AND CHARITY IN JAKARTA’S NORTH COAST RECLAMATION PROCESS THAT WILL LEAD TO INDONESIA CLEAN OF CORRUPTION - Untoro Untoro (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
The success of implementing development is one factor to assess the progress of a nation. Development as a process of change that is planned to cover all aspects of community life. Reclamation north coast of Jakarta is one form of development implementation. First aim of this study is to determine the factors that cause bribery in the reclamation of the northern coast of Jakarta. The second aim, to find out how the concept of justice and charity in the upcoming reclamation able to realize Indonesia clean of corruption. The method used the normative juridical approach (doctrinal approach). Reclamation north coast of Jakarta cause legal problems as their alleged bribery related to the discussion of the draft law and the Zoning Plan for Coastal Zone and the North Coast Jakarta revision of Regulation No. 8 of 1995 on the Implementation of Reclamation and Spatial Planning of North Coast Jakarta.  A main characteristic in this case is the behavior of public officials who violate separation principle between personal interests and the interests of society, the separation of personal finance with the community. The first conclusion, the factors that led to the occurrence of cases of bribery in the reclamation of the northern coast of Jakarta is the failure of religious education and ethics; opportunities (opportunities). Second conclusion, the concept of justice and charity in reclamation to realize Indonesia clean of corruption, as there is the relevance of faith with charity. The term ihsan (charity) always linked with the terms of faith and Islam. Ihsan has meaning making good, smarten, do good. Ihsan is witnessing the implementation of worship on the basis of the presence (rububiyah) of divinity in the eyes of the heart. Divinity in the eyes of the heart. Ihsan higher than of justice, because justice is limited to providing rights to someone who has the right, while the charity gives the person more than the right Thus, justice is only releasing obligations, while ihsan (charity) exceed liabilities, so becomes better. Keywords  : Fair ; Ihsan (Charity) ; Indonesia clean of corruption.The success of implementing development is one factor to assess the progress of a nation. Development as a process of change that is planned to cover all aspects of community life. Reclamation north coast of Jakarta is one form of development implementation. First aim of this study is to determine the factors that cause bribery in the reclamation of the northern coast of Jakarta. The second aim, to find out how the concept of justice and charity in the upcoming reclamation able to realize Indonesia clean of corruption. The method used the normative juridical approach (doctrinal approach). Reclamation north coast of Jakarta cause legal problems as their alleged bribery related to the discussion of the draft law and the Zoning Plan for Coastal Zone and the North Coast Jakarta revision of Regulation No. 8 of 1995 on the Implementation of Reclamation and Spatial Planning of North Coast Jakarta.  A main characteristic in this case is the behavior of public officials who violate separation principle between personal interests and the interests of society, the separation of personal finance with the community. The first conclusion, the factors that led to the occurrence of cases of bribery in the reclamation of the northern coast of Jakarta is the failure of religious education and ethics; opportunities (opportunities). Second conclusion, the concept of justice and charity in reclamation to realize Indonesia clean of corruption, as there is the relevance of faith with charity. The term ihsan (charity) always linked with the terms of faith and Islam. Ihsan has meaning making good, smarten, do good. Ihsan is witnessing the implementation of worship on the basis of the presence (rububiyah) of divinity in the eyes of the heart. Divinity in the eyes of the heart. Ihsan higher than of justice, because justice is limited to providing rights to someone who has the right, while the charity gives the person more than the right Thus, justice is only releasing obligations, while ihsan (charity) exceed liabilities, so becomes better. Keywords  : Fair ; Ihsan (Charity) ; Indonesia clean of corruption.The success of implementing development is one factor to assess the progress of a nation. Development as a process of change that is planned to cover all aspects of community life. Reclamation north coast of Jakarta is one form of development implementation. First aim of this study is to determine the factors that cause bribery in the reclamation of the northern coast of Jakarta. The second aim, to find out how the concept of justice and charity in the upcoming reclamation able to realize Indonesia clean of corruption. The method used the normative juridical approach (doctrinal approach). Reclamation north coast of Jakarta cause legal problems as their alleged bribery related to the discussion of the draft law and the Zoning Plan for Coastal Zone and the North Coast Jakarta revision of Regulation No. 8 of 1995 on the Implementation of Reclamation and Spatial Planning of North Coast Jakarta.  A main characteristic in this case is the behavior of public officials who violate separation principle between personal interests and the interests of society, the separation of personal finance with the community. The first conclusion, the factors that led to the occurrence of cases of bribery in the reclamation of the northern coast of Jakarta is the failure of religious education and ethics; opportunities (opportunities). Second conclusion, the concept of justice and charity in reclamation to realize Indonesia clean of corruption, as there is the relevance of faith with charity. The term ihsan (charity) always linked with the terms of faith and Islam. Ihsan has meaning making good, smarten, do good. Ihsan is witnessing the implementation of worship on the basis of the presence (rububiyah) of divinity in the eyes of the heart. Divinity in the eyes of the heart. Ihsan higher than of justice, because justice is limited to providing rights to someone who has the right, while the charity gives the person more than the right Thus, justice is only releasing obligations, while ihsan (charity) exceed liabilities, so becomes better. Keywords  : Fair ; Ihsan (Charity) ; Indonesia clean of corruption.The success of implementing development is one factor to assess the progress of a nation. Development as a process of change that is planned to cover all aspects of community life. Reclamation north coast of Jakarta is one form of development implementation. First aim of this study is to determine the factors that cause bribery in the reclamation of the northern coast of Jakarta. The second aim, to find out how the concept of justice and charity in the upcoming reclamation able to realize Indonesia clean of corruption. The method used the normative juridical approach (doctrinal approach). Reclamation north coast of Jakarta cause legal problems as their alleged bribery related to the discussion of the draft law and the Zoning Plan for Coastal Zone and the North Coast Jakarta revision of Regulation No. 8 of 1995 on the Implementation of Reclamation and Spatial Planning of North Coast Jakarta.  A main characteristic in this case is the behavior of public officials who violate separation principle between personal interests and the interests of society, the separation of personal finance with the community. The first conclusion, the factors that led to the occurrence of cases of bribery in the reclamation of the northern coast of Jakarta is the failure of religious education and ethics; opportunities (opportunities). Second conclusion, the concept of justice and charity in reclamation to realize Indonesia clean of corruption, as there is the relevance of faith with charity. The term ihsan (charity) always linked with the terms of faith and Islam. Ihsan has meaning making good, smarten, do good. Ihsan is witnessing the implementation of worship on the basis of the presence (rububiyah) of divinity in the eyes of the heart. Divinity in the eyes of the heart. Ihsan higher than of justice, because justice is limited to providing rights to someone who has the right, while the charity gives the person more than the right Thus, justice is only releasing obligations, while ihsan (charity) exceed liabilities, so becomes better.Keywords  : Fair ; Ihsan (Charity) ; Indonesia clean of corruption.